MET-EGFR dimerization in lung adenocarcinoma is dependent on EGFR mtations and altered by MET kinase inhibition. - Elena Ortiz-Zapater; Richard W Lee; William Owen; Gregory Weitsman; Gilbert Fruhwirth; Robert G Dunn; Michael J Neat; Frank McCaughan; Peter Parker; Tony Ng; George Santis (PLoS ONE)
Advanced lung cancer has poor survival with few therapies. EGFR tyrosine kinase inhibitors (TKIs) have high response rates in patients with activating EGFR mutations, but acquired resistance is inevitable. Acquisition of the EGFR T790M mutation causes over 50% of resistance; MET amplification is also common. Preclinical data suggest synergy between MET and EGFR inhibitors. We hypothesized that EGFR-MET dimerization determines response to MET inhibition, depending on EGFR mutation status, independently of MET copy number. We tested this hypothesis by generating isogenic cell lines from NCI-H1975 cells, which co-express L858R and T790M EGFR mutations, namely H1975L858R/T790M (EGFR TKI resistant); H1975L858R (sensitized) and H1975WT (wild-type). We assessed cell proliferation in vitro and tumor growth/stroma formation in derived xenograft models in response to a MET TKI (SGX523) and correlated with EGFR-MET dimerization assessed by Förster Resonance Energy Transfer (FRET). SGX523 significantly reduced H1975L858R/T790M cell proliferation, xenograft tumor growth and decreased ERK phosphorylation. The same was not seen in H1975L858R or H1975WT cells. SGX523 only reduced stroma formation in H1975L858R. SGX523 reduced EGFR-MET dimerization in H1975L858R/T790M but induced dimer formation in H1975L858R with no effect in H1975WT. Our data suggests that MET inhibition by SGX523 and EGFR-MET heterodimerisation are determined by EGFR genotype. As tumor behaviour is modulated by this interaction, this could determine treatment efficacy.